Antibacterial Activity Test of Staphylococcus aureus Coffee Fruit Peel Extract Solid Soap - Mega Karina Putri; Eni Kartika Sari; Beta Ria Erika Marita Dellima (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2025)
Bacterial skin infections remain a significant health concern, with Staphylococcus aureus being one of the common pathogens capable of infecting human skin. Preventive measures against such infections include maintaining personal hygiene, particularly through the use of cleansing products such as bath soaps. Fruit peels are known to contain bioactive compounds, namely alkaloids, flavonoids, and phenols, that exhibit antibacterial properties. To enhance their usability, coffee fruit peels can be processed into extracts and formulated into transparent solid soap preparations. This study aimed to formulate solid soap containing coffee fruit peel extract and evaluate its antibacterial activity. The research employed an experimental method comprising several stages: material preparation, extract production, soap formulation, and evaluation of physical properties. These evaluations included organoleptic assessment, pH measurement, foam height and stability, free alkali content, and antibacterial activity testing. The results showed that the transparent solid soap met the criteria for a good-quality solid preparation. Among the tested formulations, Formula 3 demonstrated the highest antibacterial activity.